1986
DOI: 10.1079/bjn19860124
|View full text |Cite
|
Sign up to set email alerts
|

The effect of forage species and stage of harvest on the processes of digestion occurring in the rumen of cattle

Abstract: 1. Pure swards of perennial ryegrass (Lolium perenne L. cv. Melle) or white clover (Trifolium repens L. cv. Blanca) were harvested daily as either primary growth (May--June) or mid-(July) and late-(August-September) season 4-week regrowths and offered to Friesian steers at two levels of feed allowance (1 8 and 24 g dry matter (DM)/kg live weight), to examine the effect of forage species and stage of harvest on nutrient digestion and supply.2. The early-and mid-season grasses had low nitrogen (23 g/kg DM) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0
5

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 14 publications
8
39
0
5
Order By: Relevance
“…Second over-supply of NH, to the liver may be potentially toxic and the studies of Symonds et al (198 1) have clearly demonstrated the consequence of hepatic NH, leakage when NH, load to the animal's tissues was elevated experimentally. Third the incidence of bloat, as seen with legume diets, may in part be related to the rapid rates of digestion and protein solubilization of fresh forage which occur in the rumen following ingestion (Beever et al 19866). In these regards the results of the present experiment with respect to the untreated forages confirm previous experimental findings (Beever et al 1985(Beever et al , 1986aUlyatt et al 1981).…”
Section: Discussionsupporting
confidence: 82%
“…Second over-supply of NH, to the liver may be potentially toxic and the studies of Symonds et al (198 1) have clearly demonstrated the consequence of hepatic NH, leakage when NH, load to the animal's tissues was elevated experimentally. Third the incidence of bloat, as seen with legume diets, may in part be related to the rapid rates of digestion and protein solubilization of fresh forage which occur in the rumen following ingestion (Beever et al 19866). In these regards the results of the present experiment with respect to the untreated forages confirm previous experimental findings (Beever et al 1985(Beever et al , 1986aUlyatt et al 1981).…”
Section: Discussionsupporting
confidence: 82%
“…Total VFA concentrations were within ranges reported for fresh forage diets, although the proportion of acetate was lower and propionate higher than has been reported (Beever et al 1986a(Beever et al , 1986bvan Vuuren et al 1992;Holden et al 1994;Berghazi et al 1996;Mackle et al 1996;Carruthers et al 1997). The ratio of acetate:propionate averaged 2.1 for all diets, ccompared with ratios of 3.0 to 4.2 reported for pasture.…”
Section: N Intakementioning
confidence: 62%
“…Using the Cornell Net Carbohydrate and Protein System model, predicted a 1.8-kg/d reduction in milk production due to urea synthesis for cows consuming pasture. Beever et al (1986) found that N in ryegrass pasture degraded in the rumen at a rate of 13 to 14%/h with 6.4 to 11.7% instantly degradable and 89.3 to 92.9% potentially degradable. Theoretically, a carbohydrate source with a degradation rate of 13 to 14%/h would be the best choice to optimize N capture when cows are grazing grass pasture.…”
Section: Introductionmentioning
confidence: 99%